Colorectal cancer migration and invasion initiated by microRNA-106a. - Bo Feng (Public Library of Science (PLoS), 2012)
MicroRNAs have been implicated in the regulation of several cellular signaling pathways of colorectal cancer (CRC) cells. Although emerging evidence proves that microRNA (miR)-106a is expressed highly in primary tumor and stool samples of CRC patients; whether or not miR-106a mediates cancer metastasis is unknown. We show here that miR-106a is highly expressed in metastatic CRC cells, and regulates cancer cell migration and invasion positively in vitro and in vivo. These phenotypes do not involve confounding influences on cancer cell proliferation. MiR-106a inhibits the expression of transforming growth factor-β receptor 2 (TGFBR2), leading to increased CRC cell migration and invasion. Importantly, miR-106a expression levels in primary CRCs are correlated with clinical cancer progression. These observations indicate that miR-106a inhibits the anti-metastatic target directly and results in CRC cell migration and invasion.